Kalecki on Financing Development: An Approach to the Macroeconomics of the Semi-industrialised Economy. - FitzGerald, E (1990)
Kalecki's FINANCING ECONOMIC DEVELOPMENT (FED) has long been regarded as a classic demonstration of the wagegoods supply constraint on growth. The application of the formal analytical methods used elsewhere in his work (and a more realistic wagegoods supply function) allows a comprehensive Kaleckian model of the industrializing economy to be built up from the two versions of the FED. Three commodity markets (for food, manufactors and capital good), foreign trade and income distribution underpin an interesting specification of the financial-sector with savings, investment, fiscal and monetary balances. This elucidation of Kalecki both clarifies his fundamental contribution to modern structuralist economics and demonstrates that stabilization policy should be based on fiscal rather than monetary variables.